Mempersiapkan Keuangan dalam Menghadap Masa Purnabakti - Ana rusmardiana (Universitas Indraprasta PGRI, 2019)
One of the retirement preparations is preparation in finance, financial planning is an effort that aims to achieve financial freedom in old age. This discussion describes the relevance of the human life cycle with financial planning in an effort to deal with retirement. To deal with retirement is not always with entrepreneurship skills but there are 5 (five) other factors that also influence it, namely: reorganizing finance, drafting a reserve fund by not spending all income earned, reviewing if necessary controlling debt-debt, buying insurance and investing. Intended to motivate workers early in preparing their finances in order to deal with their retirement later. A descriptive qualitative approach using the library method and interview method for a workshop company that is providing pre-retirement preparation training to some of its employees.